Longer race distance predicts gastrointestinal illness-related medical encounters in 153,208 endurance runner race starters - SAFER XVI - Pillay, S.; Schwellnus, M. P.; Grant, C.; Swanevelder, S.; Jansen van Rensburg, A.; Jordaan, E. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Gastrointestinal illness-related (GITill) medical encounters during distance running range from mild to debilitating. The objective of this study was to identify factors that may predict GITill among 21.1 km and 56 km race starters. METHODS: This is a cross-sectional analysis of data collected prospectively over 8 years at the Two Oceans 56 km and 21.1 km races with 153,208 race starters. GITill encounters requiring medical attention on race day were recorded by medical staff. Risk factors associated with GITill explored in univariate models included: race distance (21.1 km; 56 km), sex, age group, running experience, running speed, and environmental factors (wet-bulb temperature, wind speed and humidity). Incidence (per 100,000 race starters; 95% CI) and incidence ratios (IR) (with 95% CI) are reported. RESULTS: The incidence of GITill encounters was 60 (95%CI: 50-80) (1/1667 race starters). A longer race distance (56 km vs. 21.1 km) was the strongest predictor of GITill (IR=4.3; 95% CI: 2.7-6.7) (P<0.0001). Among the 56 km race starters, slower running speed (km/h) was a predictor of GITill (IR=1.63; 95%CI:1.2-2.3) (P=0.0024). Neither age group, nor running experience or any environmental factors (wet-bulb temperature, wind speed, humidity) were associated with a higher risk of GITill. CONCLUSIONS: Medical teams, responsible for care at longer race distances, can expect a higher incidence of GITill that require medical attention compared with shorter race distances. Slower runners competing in ultramarathons are a subgroup at higher risk of GITill. These data can assist medical teams at events to improve and plan medical care, target runner education and establish prevention strategies to reduce GITill in runners.